2016
DOI: 10.1111/gbb.12297
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the REG‐CTNNA2 region of chromosome 2 and NEIL3 associated with impulsivity in a Native American sample

Abstract: Impulsivity is a multi-faceted construct that, while characterized by a set of correlated dimensions, is centered around a core definition that involves acting suddenly in an unplanned manner without consideration for the consequences of such behavior. Several psychiatric disorders include impulsivity as a criterion, and thus it has been suggested that it may link a number of different behavioral disorders, including substance abuse. Native Americans experience some of the highest rates of substance abuse of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Our preliminary genome-wide association analyses revealed a promising hit near the CTNNA2 gene in chromosome 13, which encodes Catenin alpha-2. This is of particular interest because CTNNA2 has been previously implicated in human association studies, including a GWGAS of anxiety disorders, and encodes a neuron-specific catenin that is important for cellto-cell adhesion and synaptic plasticity, is expressed throughout cortical and subcortical structures, and is implicated in numerous studies of IT-related phenotypes (17, [66][67][68][69][70][71][72][73]. The association analysis presented here does not constitute evidence for a definitive association between CTNNA2 and infant IT in the rhesus monkey.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our preliminary genome-wide association analyses revealed a promising hit near the CTNNA2 gene in chromosome 13, which encodes Catenin alpha-2. This is of particular interest because CTNNA2 has been previously implicated in human association studies, including a GWGAS of anxiety disorders, and encodes a neuron-specific catenin that is important for cellto-cell adhesion and synaptic plasticity, is expressed throughout cortical and subcortical structures, and is implicated in numerous studies of IT-related phenotypes (17, [66][67][68][69][70][71][72][73]. The association analysis presented here does not constitute evidence for a definitive association between CTNNA2 and infant IT in the rhesus monkey.…”
Section: Discussionmentioning
confidence: 85%
“…Most excitingly Levey et al, (2019)(17) found SNPs in human CTNNA2 to be associated with anxiety disorders in their GWGAS (1/31 genes tested above). Consistent with a shared genetic substrate between anxiety, depression, and addiction, GWAS studies in humans have also implicated variation in the CTNNA2 gene in impulsivity (67), excitement seeking (68), depression with comorbid substance abuse (69), substance dependence (70), anorexia(71), and chronic pain (72). As noted in the main manuscript, the association analysis presented here does not constitute evidence for a definitive association between CTNNA2 and infant IT in the rhesus monkey.…”
Section: Supplemental Materialsmentioning
confidence: 92%
“…For every outcome variable, the type I error rate was set to a two-sided 0.05, and the minor allele frequency (MAF) range was hypothesized between 0.01 and 0.5 by 0.01. Based on previous studies, the effect size was expected to be β = 0.08 [ 9 ] or β = 1.62 [ 7 ] in an additive model, for every variable. The range of potential MAF values and the two hypothesized effect sizes resulted in a range of statistical power values to detect the CTNNA2 SNP effects.…”
Section: Methodsmentioning
confidence: 99%
“…It has been implicated in bipolar disorder [ 2 ], adult attention-deficit/hyperactivity disorder (ADHD) [ 3 ], alcoholism [ 4 ], schizophrenia, and general cognitive function [ 5 ], as well as in success in smoking cessation [ 6 ]. Moreover, it has shown associations with personality traits and endophenotypes that lie on possible pathways between genes and disorders, namely: impulsivity, which covers both novelty seeking and lack of planning [ 7 ], as well as a common visual endophenotype of schizophrenia and autism spectrum disorder, namely deficits in sensitivity to visual stimuli of a low spatial and high temporal frequency [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that impulsivity questionnaires such as the UPPS-P are likely to be consistent across ethnicities (Stevens, Blanchard, Shi, & Littlefield, 2018). The role of genetics in potential impulsivity phenotypes within and between ethnicities has recently been examined in substance misuse (Ehlers et al, 2016), and risk-taking behaviour (Strawbridge et al, 2018). Strawbridge and colleagues in particular found that there were greater differences between sexes than between ethnicities in terms of the potential role of genetics on risk-taking behaviour.…”
Section: Self-harm and Impulsivity In The Context Of Ethnic Minority mentioning
confidence: 99%